DEVELOPMENT OF OFFLINE DIGITAL MEDIA PORTALS TO IMPROVE SCHOOL LITERATION IN SMKN 1 BENGKULU CENTRAL - Lovi Triono; Turdjai Turdjai (UNIB Press, 2018)
The purpose of this study is to develop a digital media based offline learning resource portal to improve school literacy. The research method uses the